Pengaruh Perbedaan Gender dan Inklusi Keuangan Terhadap Kapabilitas Pemasaran Asuransi Syariah Pada Organisasi NU Padangsidempuan - Situmeang, Saidah Hayati; Imsar, Imsar; Syarbaini, Ahmad Muhaisin B. (Jayapangus Press, 2024)
This research aims to find out how the influence of gender differences and financial inclusion on sharia insurance marketing capabilities in the NU organization Padangsidempuan. Bannier & Schwarz research, which says that The role of gender differences can have implications for financial literacy and inclusion finance. The type of research used is quantitative research with methods multiple linear regression. The data analysis technique used in this research is purposive sampling technique with hypothesis testing used includes the T test, F test, and coefficient of determination. The sample in this research is the large organization NU in the last 5 years (2018-2022). The results of this research show that gender differences have no effect on insurance marketing capabilities sharia. Meanwhile, the financial inclusion variable has a significant effect on sharia insurance marketing capabilities. Simultaneously variable differences gender and financial inclusion have a significant effect on marketing capability sharia insurance. This research has an Adjusted R Square value of 0.748 or 74.8%. This shows that the dependent variable or marketing capability Sharia insurance can be explained by dependent variables or gender differences and financial inclusion with a score of 74.8. While the remaining 26.2% influenced by other variables. Money was not examined in this study.